PENINGKATAN KADAR VITAMIN C BUAH TOMAT (Lycopersicum esculentum MILL.) DATARAN RENDAH DENGAN PEMBERIAN HORMON GA3 - Riky Gusti Handrian; Meiriani Meiriani; Haryati Haryati (Universitas Sumatera Utara, 2013)
Tomato is one of the fruits that are beneficial to humans. Tomato has a delicious taste and has acomposition of substances in tomatoes quite complete and well. Composition in tomatoes quiteprominent of these is the composition of vitamin A and C. With vegetables like tomatoes and otherfruits, can be processed into various food products. Nutrient composition of tomato fruit is 100grams of protein (1 g), carbohydrate (4.2 g), fat (0.3 g), calcium (5 mg), phosphorus (27 mg), iron(0.5 mg ), vitamin A (carotene) 1500 SI, vitamin B (thiamine) 60 mcg, vitamin C 40 mg. Vitaminscontained in tomatoes is necessary for the growth and health of the body. Vitamin C is useful toprevent ulcers, to maintain healthy teeth and gums, as well as protect against other diseases causedby lack of vitamin C. Even the U.S. study showed, tomatoes can be used as a preventative ofcancer, particularly prostate cancer, if eaten on a regular basis as much as 5 pieces every week. Oneof the business in order to increase the levels of vitamin C in tomatoes that growth hormone GA3application. Results of research conducted by Meiriani (2011) on the provision of GA3 on tomatoplants results obtained highest levels of vitamin C at a concentration of 450 ppm with a frequencyof 3 times is equal to 123.20 mg/100 g. This research aimed to increase in vitamin C of tomato(Lycopersicum esculentum Mill.) with the hormone GA3. This research aimed to increase vitaminof tomato (Lycopersicum esculentum Mill.) with the GA3 hormone. This Research was conducted atthe Faculty of Agriculture, Universitas Sumatera Utara about + 25 meters above sea level fromJanuary to April 2012. And arrange in randomized block design with two-factors factorialtreatments. The first factor was concentration of GA3 with four levels : 300 ppm, 450 ppm, 600ppm, 750 ppm and the second factor was frequency of GA3 with three levels, i.e : 3 time, 4 timesand 5 times. The result of research showed that application of GA3 at concentration up to 750 ppmwas significantly influenced to increased tomato vitamin C level. Interaction of both treatmentwas not significant to influenced parameter of observation.Key words : GA3, tomato, consentration, application frequency, vitamin C.